2020
DOI: 10.1155/2020/3040845
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diversity and Associated Factors among Children Aged 6-59 Months in Ethiopia: Analysis of Ethiopian Demographic and Health Survey 2016 (EDHS 2016)

Abstract: Background. Dietary diversity is one of the key elements of diet quality. Even though different measures were taken to increase dietary diversity feeding practice in Ethiopia, the problem still remains high. Therefore, this study was done to identify determinants of inadequate minimum dietary practice among children aged 6-59 months in Ethiopia. Method. Secondary analysis of the data from the 2016 Ethiopian Demographic and Health Survey was done on a weighted sample of 5161 children aged 6-59 months. Data anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 30 publications
8
23
1
Order By: Relevance
“…Other research also suggested that children’s dietary diversity has been affected by households’ economic status. 15 , 19 , 37 It could be a proxy for wealth because it reflects increased access to foods purchased outside the household. 38 We also found that child dietary diversity is significantly associated with maternal education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research also suggested that children’s dietary diversity has been affected by households’ economic status. 15 , 19 , 37 It could be a proxy for wealth because it reflects increased access to foods purchased outside the household. 38 We also found that child dietary diversity is significantly associated with maternal education.…”
Section: Discussionmentioning
confidence: 99%
“…16 In Ethiopia, there is an improvement in the proportion of children who meet the MDD, 6.3% in 2005 to 13.5% in 2016; 17 however, the levels remain unacceptably low. Previous research has revealed factors connected to children's DD such as mother's age, maternal educational level, 12,18 marital status, maternal occupation, 19 ANC visit, residence, region, child's gender, birthing sequence, childbirth interval, child's age, 18 number of under-5 children, 19 currently breastfeeding, paternal educational status, household wealth status, 12,20 family size, desire for pregnancy, media exposure, antenatal and postnatal care. 17,21 Many public health measures have been carried out across Ethiopia to improve the culture of DD and the nutritional status of children.…”
Section: Introductionmentioning
confidence: 99%
“…MDD, an indicator that measures dietary diversity was the key explanatory variable. MDDcan be defined as the proportion of children aged 6-23 months who receive four or more out of seven food groups [4,12,13,15,30]. The children were expected to consume at least four of the seven food groups in addition to breastmilk.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…The children who consumed at least four (≥4) of the food groups were said to have an adequate MDD and this was coded as "1" while the remaining children who consumed lower than four food groups were coded as "0 = inadequate". This classification and categorization were informed by literature that studied either dietary diversity alone or its association with undernutrition [4,12,13,30].…”
Section: Explanatory Variablesmentioning
confidence: 99%
See 1 more Smart Citation